THE ROLE OF B-TYPE NATRIURETIC PEPTIDE LEVELS IN PREDICTING (LIFE THREATENING) REPERFUSION ARRHYTHMIAS IN ACUTE MYOCARDIAL INFARCTION PATIENTS - Barno F. Mukhamedova; Maftuna Kh. Nazarova; Bekhzodbek O. Kazakov; Dilorom E. Abdujabborova (Central Asian Journal of Medicine, 2025)
Aim. To evaluate the role of B-type natriuretic peptide (BNP) levels in predicting reperfusion arrhythmias in acute myocardial infarction (AMI) patients. Material and methods. This study included 153 patients with AMI, hospitalized in RRCEM from January to December 2023. BNP levels were measured upon admission, and subsequently on the 1st and 3rd days after thrombolytic therapy (TLT) or percutaneous coronary intervention (PCI). 24-hour Holter monitoring was conducted to detect reperfusion arrhythmias. Results. A significant correlation was found between high initial BNP levels and the development of reperfusion arrhythmias such as ventricular premature beats, atrioventricular blocks, and paroxysmal ventricular tachycardia. BNP levels showed a significant decrease on the 1st and 3rd days post-TLT and PCI, correlating with clinical improvement. Conclusion. High initial BNP levels are associated with an increased risk of reperfusion arrhythmias in AMI patients. Monitoring BNP levels can aid in the early identification of high-risk patients and the optimization of their treatment.